ON THE TORSION OF TRACK CABLES OF JIG BACK ROPEWAYS - Korotkiy, A. A.; Khalfin, M. N.; Ivanov, B. F.; Panfilov, A. V.; Kalanchukov, I. A. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2019)
Observations of the operation of jig back rope-ways allowed us to suggest the presence of torsion of track cables of a closed structure under the influence of operational loads. In this case, the total weight of the cable and the car is a trans-verse load, and the cable itself is loaded with longitudinal resistance forces in its individual sections. The paper provides theoretical substantiation and experimental confirmation of the presence of torsional deformations of track cables of jig back ropeways under the influence of friction between the cable and the rocking saddles. A new method of rejection of such cables based on the control of torsional deformations is proposed.